Regulating freedom? : an examination of the discourse on internet regulation and freedom of expression in South Africa (2010) - Mthimkhulu, Zongile Nomfundo (My University, 2011)
As a technology designed and founded on liberal ideology and concepts of freedom of access, information and expression, the advent of the Internet has brought about much hope, and equally, much fear. For many, the internet is a medium that liberates individuals from the centralised and asymmetrical power structures of traditional mass media and other social institutions, the boundaries set by the nation and the state. For other people, the internet increases the capacity of surveillance and control. This research examined this discourse on internet regulation and freedom of expression in South Africa in the year 2010. This was a qualitative study that analysed documents in the form of newspaper articles in the year 2010 and secondary research in the form of policy documents such as bills and acts pertaining to internet regulation and freedom of speech. Interviews with informants relevant to the topic were also conducted as a secondary form of data collection. A discourse analytic approach was used as the method of analysis, together with Critical Negotiation Issues and Public Regulation Theory as a conceptual and theoretical framework, respectively. The results indicate that there are what may arguably be perceived as primary forms of regulation on the internet. These ‘forms’ have caused and are causing an intense debate in the media with regards to this. These debates were examined and the findings reveal that the majority of informants argue against regulation of any sort of the internet, the majority stating that a form of regulation curtails the right to freedom of expression which is essential to South Africa’s democracy. Noted in the findings were also a minority that argued for a form of regulation, in protecting the public against what has been deemed as the ills of the internet-pornography, paedophilia, terrorist activities and so forth